TINGKAT PENDIDIKAN DAN SIKAP IBU NIFAS TENTAG PERAWATAN LUKA PERINEUM - Lina Darmayanti Bainuan (Akademi Kebidanan Griya Husada Surabaya, 2019)
Introduction: The perineum is the area between the thighs bounded by the vulva and anus. Injury to the birth canal can occur due to an error during labor. In addition, the birth canal can also occur due to intentional acts such as episotomy. The cause of perineal infection is caused by organisms that attack the implantation or laceration due to childbirth. Based on data obtained at BPS Ny. Retno Soepomo Surabaya found that mothers who experienced perineal tears in 2016 to 2018 experienced an increase of (32.9%). Therefore this study aims to determine the description of education and postpartum mothers' attitudes about care for perineal wounds. Method: This research uses descriptive method. The study population was all postpartum mothers who controlled on the 7th day with perineal suture wounds in July with a non probability sampling technique which sampled saturated samples, with a sample of 42 people using a questionnaire as primary data and secondary data, data analysis with frequency tables and cross tabulation. Results: The results showed that postpartum mothers with low education majority of perineal wounds did not heal (85.71%) compared to postpartum mothers with higher education the majority of perineum healed wounds (75%), while postpartum mothers with postpartum mothers' attitudes were less amenable to perineum injuries not healed (81.82%) compared to postpartum mothers who had the agreed attitude the majority of perineal wounds healed (71.43%). Discussion: Mothers who take care of perineal wounds can be influenced by education and attitudes of women about care for perineal wounds. Therefore health workers should provide correct advice or instructions on how to perform perineal wound care for successful healing of perineal wounds.